Analisis Faktor Penentu Kecendrungan Orang Bermigrasi Keluar Negeri Di Kabupaten Bulukumba - Naidah, Naidah (Jurnal Ekonomi Balance, 2011)
This research aims to find out some determinants of outflow migration in Bulukumba. The required data consists of primary and secondary data. Primary data were collected through interviews with selected respondents using a pre-prepared questionnaire (questionnaire). Determination of the respondents intentionally from the number of population as many as 200 people sampled 10% (20 people) simple random sampling (simple random sampling). Furthermore, the list of questions is followed directly by the researchers while conducting in-depth interviews on several respondents. While secondary data will be collected through literature studies, reports, or other documentation contained in the office or related agencies such as village offices / sub-districts, statistical offices and other relevant agencies. The data collected in this study is further presented in the form of description to obtain an overview of the factors that affect the outflow migration that is analyzed qualitatively and quantitatively. Quantitatively used simple statistical methods through the frequency distribution table using percentages and averages and graphs.The conclusions of this study are (1) Factors driving the outflow of migration in Bontotiro Sub-district, Bulukumba District is the absence of work, the absence of workable land, low wages, and due to follow-up. (2) The outflow migration factor in Bontotiro sub-district is a high salary factor in the destination, easy work requirements, available jobs at all times, and family influences. (3) The level of income of migrants out in Bontotiro District is quite high, which ranges from Rp. 1,000,000, - hinggar Rp. 2,500,000, - upwards per month, well above the provincial minimum wage (UMP) set by the Manpower and Transmigration Office of South Sulawesi Province of Rp. 400,000, - per month.